Genetics of pain perception, COMT and postoperative pain management in children. (February 2014) - Sadhasivam, Senthilkumar; Chidambaran, Vidya; Olbrecht, Vanessa A; Esslinger, Hope R; Zhang, Kejian; Zhang, Xue; Martin, Lisa J
Background: Effective perioperative analgesia is lacking for children owing to interindividual variations and underdosing of opioids caused by fear of adverse effects. We investigated the role of COMT SNPs on postoperative pain management in children.Methods: One hundred and forty nine children undergoing adenotonsillectomy were enrolled. The associations of four COMT SNPs (rs6269, rs4633, rs4818 and rs4680) with postoperative pain were analyzed and outcome measures included maximum pain scores, need for postoperative opioid interventions and postoperative morphine requirements.Results: We detected an association of postoperative opioid intervention need with all four COMT SNPs. Minor allele carriers of COMT SNPs were approximately three-times more likely to require analgesic interventions than homozygotes of major alleles (p-value range: 0.0031–0.0127; odds ratio range: 2.6–3.1). In addition, significant association was detected between maximum Face, Leg, Activity, Consolability, Cry (FLACC) pain scores and three COMT SNPs (rs6269, rs4633 and rs4680). Haplotype 1 (ATCA: 51.3%) and Haplotype 2 (GCGG: 36.2%) are more frequent. Haplotype 2 was associated with higher odds of intravenous analgesic intervention need in postanesthesia recovery unit with an odds ratio of 2.6 (95% CI: 1.2–5.4; p-value = 0.022).Conclusion: COMT SNPs may play a significant role in interindividual variation in postoperative pain perception and postoperative morphine requirements in children. Original submitted 16 August 2013; Revision submitted 13 December 2013